Perlindungan Hukum Hak Para Anak Terduga Pelaku Tindak Pidana Pencabulan dan/atau Persetubuhan Dalam Proses Penyidikan: - - Naldo, Rony Andre Christian; Pasaribu, Muldri Pudamo James; Hutasoit, Arianto Suhardhiman (Universitas Medan Area, 2024)
This research aims to examine the rights of children suspected of committing crimes of sexual abuse and/or sexual intercourse. Children's rights are part of human rights, which must be guaranteed, protected and fulfilled. In the event that the investigation process is carried out, the Police as a part of the Government agency, are obliged to guarantee, protect and fulfill the various rights of these children, as stipulated in Article 3 of Law Number 11 of 2012. The problem is focused on the implementation of legal protection of the rights of children. children suspected of committing criminal acts of sexual immorality and/or sexual intercourse in the process of being investigated by the Police. In order to approach this problem, a theoretical reference from Satjipto Rahardjo is used. Data was collected through primary legal materials, secondary legal materials and tertiary legal materials, and analyzed qualitatively. This study concludes that the legal protection of the rights of children suspected of committing crimes of sexual abuse and/or sexual intercourse during the investigation process at the Police has not been fully implemented. This is because there is no infrastructure in the form of a special detention room for children suspected of committing criminal acts.